PENGARUH INVESTASI, PDRB DAN PENYERAPAN TENAGA KERJA TERHADAP JUMLAH PENDUDUK MISKIN - Agus Budi Purnomo (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Introduction: During 2009-2013, the percentage of poor people in East Java was always above the national level. Based on this background, this study aims to examine and analyze the effect of investment, Gross Regional Domestic Product (GRDP), and labor absorption on the number of poor people in districts and cities in East JavaMethods: This study uses the path analysis method. This method was chosen because it is able to explain the direct and indirect effects between the independent variables and between the independent variables and the dependent variable based on a model built from previous theory and research.Results: The results showed that investment directly had a positive effect on GRDP and employment. Meanwhile, GDP has a direct negative effect on the number of poor people, and employment has a direct positive effect on the number of poor people. So that investment indirectly has a negative effect on the number of poor people through PDRB, and investment indirectly has a positive effect on the number of poor people through employment.Conclusion and suggestion: Regencies or cities whose economy is dominated by the industrial, service and trade sectors such as Sidoarjo regency, Gresik regency, Surabaya city, Malang city and the majority of other cities in East Java Province, which so far have low labor absorption, require labor intensive investment. so as to be able to absorb more labor which in turn will reduce the number of poor people.